A study on potential development of fisheries resources in the coastal area of Tolitoli Regency - ., Yuliani; Mantjoro, Eddy; Wantasen, Adnan; Lasut, Markus T (AQUATIC SCIENCE & MANAGEMENT, 2013)
Tolitoli is one of regencies in Central Sulawesi province that has fisheries and marine resources which are potentially exploited and developed. The total area of Tolitoli regency is 4079.77 km² land and 3008.59 oceans km² area with a long range 453.98 km coastline. Administratively, Tolitoli consists of 10 districts (9 of which are districts that have coastal areas), 104 villages (60 of which are coastal villages) and 43 islands (13 inhabited islands and 30 uninhabited islands) which are small islands scattered along the coastal areas. In addition, Tolitoli have 3 outer islands bordering neighboring country: Lingayan Island, Island Salando and Dolangan Island. Resource potential and development of coastal fisheries Tolitoli has an area of ​​707 ha of mangrove and coral 11568.5 ha. For mariculture potential is around 2011, 10.800 ha with a total production 702.4 tonnes, inland aquaculture 4250 ha with a total production of 499 tonnes. Cathing fisheries was exploited in 2011 for approximately 30009.21 tonnes/year by the number of RTP 2500 households. As for the potential location of fish processing is 29 000 M² with a production of 210.3 tonnes. For tourism potential there are 14 potential tourism attractions that can be favored by local governments to be developed© Kabupaten Tolitoli merupakan salah satu  kabupaten di Propinsi Sulawesi Tengah yang memiliki sumberdaya perikanan dan kelautan yang potensial untuk dimanfaatkan dan dikembangkan. Luas Kabupaten Tolitoli yaitu 4.079,77 km² daratan dan 3.008,59  km² wilayah lautan dengan panjang  garis pantai berkisar 453,98 km. Secara administratif, Kabupaten Tolitoli terdiri dari 10 kecamatan (9 di antaranya merupakan kecamatan yang mempunyai wilayah pesisir) dan jumlah desa sebanyak 104 (jumlah desa pesisir sebanyak 60) serta mempunyai 43 pulau (13 pulau berpenghuni dan 30 pulau tidak berpenghuni) yang merupakan pulau-pulau kecil yang tersebar di sepanjang wilayah pesisir. Selain itu, Kabupaten Tolitoli memiliki 3 pulau terluar yang berbatasan dengan negara tetangga Malaysia, yaitu Pulau Lingayan, Pulau Salando, dan Pulau Dolangan.Potensi sumberdaya dan pengembangan perikanan pesisir Kabupaten Tolitoli memiliki ekosistem mangrove seluas 707 Ha, Karang 11.568,5 Ha.Untuk potensi budidaya laut tahun 2011 seluas10.800 Ha dengan jumlah produksi 702,4 ton,budidaya perikanan darat/tambak  4.250 Ha dengan jumlah produksi 499 ton. Potensi perikanan tangkap yang termanfaatkan pada tahun 2011 sekitar 30.009,21 ton/tahun dengan jumlah RTP 2.500 KK. Sedangkan untuk luas lokasi potensi pengolahan hasil perikanan yaitu 29.000 M² dengan produksi 210,3 ton. Untuk potensi pariwisata terdapat 14 objek wisata yang dapat diunggulkan oleh pemerintah daerah untuk dikembangkan©